2022
DOI: 10.1177/15347354221096080
|View full text |Cite
|
Sign up to set email alerts
|

Advances in the Study of Circadian Genes in Non-Small Cell Lung Cancer

Abstract: Circadian genes regulate several physiological functions such as circadian rhythm and metabolism and participate in the cytogenesis and progression of various malignancies. The abnormal expression of these genes in non-small cell lung cancer (NSCLC) is closely related to the clinicopathological features of NSCLC and may promote or inhibit NSCLC progression. Circadian rhythm disorders and clock gene abnormalities may increase the risk of lung cancer in some populations. We collected 15 circadian genes in NSCLC,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 62 publications
0
1
0
Order By: Relevance
“…Hence, biological rhythm dysregulation may lead to abnormal cell proliferation, cell resistance to apoptosis, and increased gene mutation rates, which may induce tumorigenesis (19). Further studies have shown that changes in biological rhythms are closely related to the occurrence of thyroid, breast, prostate, colorectal, liver, lung, and other cancers (20)(21)(22)(23). At the mammalian cell level, the circadian rhythm system is a transcriptional translation feedback loop based on the oscillatory compilation of circadian clock gene expression (24,25) and involves 14 core circadian clock genes as well as various circadian clock control genes.…”
Section: W I T H D R a W N S E E M A N U S C R I P T D O I F O R D E ...mentioning
confidence: 99%
“…Hence, biological rhythm dysregulation may lead to abnormal cell proliferation, cell resistance to apoptosis, and increased gene mutation rates, which may induce tumorigenesis (19). Further studies have shown that changes in biological rhythms are closely related to the occurrence of thyroid, breast, prostate, colorectal, liver, lung, and other cancers (20)(21)(22)(23). At the mammalian cell level, the circadian rhythm system is a transcriptional translation feedback loop based on the oscillatory compilation of circadian clock gene expression (24,25) and involves 14 core circadian clock genes as well as various circadian clock control genes.…”
Section: W I T H D R a W N S E E M A N U S C R I P T D O I F O R D E ...mentioning
confidence: 99%
“…Knockdown of BMAL1 disrupts circadian rhythm and enhances migration or invasion in lung cancer, breast cancer, and glioma cells (170, 171). Loss of BMAL1 may contribute to lung cancer development by activating KRAS and cancer-regulating genes such as P53 and c-Myc (172). Overexpression of BMAL1 inhibits proliferation and increases sensitivity to oxaliplatin in CRC cell lines and HCT116 cell models in vivo (174).…”
Section: Baml1mentioning
confidence: 99%
“…clock genes have been identified in mammals that possess homologous genes also found in Drosophila melanogaster [9]. However, two genes, Clock and Bmal1, have been shown to play a significant role in maintaining sleep homeostasis [10].…”
Section: Introductionmentioning
confidence: 99%